Awareness of Eye Donation among University Students - Pokharel, Shailesh Mani; Lamichhane, Nabin; Regmi, Sushil (Journal of Nepal Health Research Council, 2024)
Backgrounds: Eye donation is an act of donating, one’s eyes, mostly the cornea after his/her death. According to World Health Organization (WHO) estimates every 5 second, someone goes blind. There are currently about 45 million blind people in the world which increases by 1 to 2 million every year. The study aimed to identify and explore the awareness of eye donation among university students in Morang, Nepal. Methods: A descriptive cross-sectional study was conducted on Undergraduate Students of Purbanchal University School of Health Sciences a constituent college of Purbanchal University situated in Sundarharaicha Municipality of Morang District of Nepal. Population proportionate simple random sampling technique was applied to allocate the sample size. Results: Among the total of 177 respondents, 22.0% are from the Pharmacy faculty, 22.6% from Public Health, and 55.4% from Nursing. Out of the total respondents, 98.9% were aware of eye donation, while only 1.1% had no awareness. About 86.9%, of the respondents correctly identified the cornea as a donatable part. However, a smaller percentage mentioned the retina (4.0%), eye ball (6.9%), and lens (2.3%).Conclusions: The findings of the study on awareness of eye donation suggest the need for targeted educational interventions to enhance understanding the parts of eye for donation and avoiding the misconceptions about various aspects of eye donation among Health Sciences students. Keywords: Awareness; eye donation; health science students.